Integrated Reporting: A Bibliometric Analysis of Research Development and Core Themes (2011–2026) - Loso Judijanto (West Science Accounting and Finance, 2026)
This study aims to map the development, intellectual structure, and core themes of integrated reporting research over the period 2011–2026 using a bibliometric approach. Data were collected from the Scopus database and analyzed using VOSviewer to examine publication trends, keyword co-occurrence, thematic clusters, and temporal evolution. The findings reveal that although integrated reporting has gained increasing scholarly attention, the research landscape remains highly interdisciplinary and fragmented, with dominant themes still centered on methodological rigor, empirical analysis, and evidence-based approaches. Cluster analysis identifies key thematic areas including governance and accountability, sustainability and ESG, value creation, and reporting quality, while overlay visualization indicates a shift from foundational research toward emerging topics such as artificial intelligence, decision-making, and climate-related issues. Density analysis further shows that integrated reporting and sustainability-related themes, while growing, remain less developed compared to established methodological domains. This study contributes to the literature by providing a comprehensive mapping of integrated reporting research and highlighting opportunities for future studies to strengthen theoretical integration, expand empirical contexts, and position integrated reporting as a central framework in corporate reporting and sustainability discourse.